2020
DOI: 10.47102/annals-acadmedsg.202090
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in Sepsis Management—What is the Way Forward?

Abstract: Sepsis is life-threatening and might potentially progress from dysregulation to severe organ dysfunction. It is recognised by the World Health Organisation as a global health priority. The mortality rate for sepsis has decreased in many countries, and this is credited to the earlier recognition and treatment of this complex syndrome. In 2002, the Surviving Sepsis Campaign was launched, and there have been several revisions to the sepsis recommendations therefrom. The latest sepsis guidelines focus on viral as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Despite having similar admission characteristics, patients in the immunomodulation group required greater PICU support compared to those in the nonimmunomodulation group, including invasive ventilation (38/54, 70.4% vs 26/55, 47.3%; P=0.019) and inotropes (41/54, 75.9% vs 32/55, 58.2%; P=0.067), though this did not reach statistical significance. Ventilator-and ICU-free days were also reduced in the immunomodulator group (20 [0-28] vs 25 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]; P=0.038 and 15 [0-24] vs 22 (9-26); P=0.024, respectively). In this sepsis cohort, a total of 31 deaths (28.4%) occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite having similar admission characteristics, patients in the immunomodulation group required greater PICU support compared to those in the nonimmunomodulation group, including invasive ventilation (38/54, 70.4% vs 26/55, 47.3%; P=0.019) and inotropes (41/54, 75.9% vs 32/55, 58.2%; P=0.067), though this did not reach statistical significance. Ventilator-and ICU-free days were also reduced in the immunomodulator group (20 [0-28] vs 25 [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]; P=0.038 and 15 [0-24] vs 22 (9-26); P=0.024, respectively). In this sepsis cohort, a total of 31 deaths (28.4%) occurred.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of immunotherapy in treating sepsis has been met with mixed results. 12,13 Recent clinical trials involving corticosteroids showed mixed results regarding mortality and hospitalisation. 14,15 A Cochrane review on intravenous immunoglobulin (IVIG) revealed mortality benefit in adults with sepsis but not in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…After bacteria or toxins enter the blood circulation, they cause immune-inflammatory mechanism cascading waterfall-like outbreaks, which release a large number of cytokines and inflammatory mediators, resulting in excessive systemic inflammatory response syndrome. [16] Patients with severe sepsis are prone to distant organ insufficiency and inadequate blood perfusion to the visceral tissues because of immune-inflammatory injury, with an extremely high incidence of multiple organ function injury or failure, they need comprehensive and cluster treatment during the initial stage. [17] The timely identification of the severity of the disease and the accurate judgment of the prognosis is beneficial to the timely adjustment and improvement of the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…After bacteria or toxins enter the blood circulation, they cause immune-inflammatory mechanism cascading waterfall-like outbreaks, which release a large number of cytokines and inflammatory mediators, resulting in excessive systemic inflammatory response syndrome. [16]…”
Section: Discussionmentioning
confidence: 99%
“…2,3 If sepsis patients do not receive timely and effective treatment at the early stage of the disease, the disease may worsen to a severe level and induce complications such as shock and multiple organ dysfunction syndrome (MODS), which may lead to death in severe cases. 3,4 Clinical studies have found that the earlier antimicrobial drugs are applied after sepsis is confirmed, the greater the benefit to the patient, and intravenous antimicrobial drug therapy should be started as soon as possible within 1 h. 5 Before that, microbial cultures should be obtained and microbiologically confirmed, and antimicrobial drugs should be adjusted according to the drug sensitivity results and clinical signs and symptoms. 4 Traditional pathogenic microbial culture methods and diagnostic pathogenesis found that the most common clinical pathogenic bacteria are gram-negative bacteria, followed by gram-positive bacteria, fungi, anaerobic bacteria, and parasites.…”
Section: Introductionmentioning
confidence: 99%